EFEK INFUSA DAUN SIRSAK (Annona muricata) PADA KADAR LDL DAN HDL SERUM TIKUS WISTAR (Rattus norvegicus) YANG DIINDUKSI DIET TINGGI LEMAK DAN FRUKTOSA - Adnanda Maulana (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2019)
Introduction : High fat and fructose diet (HFFD) can lead to dyslipidemia due to the increasing of the level of the cholesterol, triglycerides, LDL and the decreasing level of HDL. Soursop leaves (Annona muricata) contain active compounds which can potentially improve the lipid profiles. This study investigated the effect of soursop leaves infusion in LDL and HDL serum levels of Wistar rats induced by HFFD.Method : This study used Wistar rats aged 8-10 weeks as samples with initial body weight between 175-200g. The rats were placed into 5 groups called negative control group (N), positive control group (P), treatment 1 group (T1), treatment 2 group (T2) and treatment 3 group (T3) with 5 rats for each group. The HFFD was given for 10 weeks leading to dyslipidemia in group P, T1, T2, and T3. Soursop leaves infusion were given to T1 (100 mg/kg b.w.), T2 (200 mg/kg b.w.), and T3 (400 mg/kg b.w.) by using feeding tube, as an addition to HFFD in 10 weeks. At the end of the study, LDL and HDL serum levels were measured using the ABX Pentra procedure. Data will be analyzed by Mann Whitney test with a significance level p <0.05.Results : HFFD can increase the LDL serum levels and can decrease HDL serum levels significantly (p<0.05). The addition of soursop leaves infusion at dose of 200 mg / kg b.w. decreased LDL serum levels about 45% compared with positive control (p <0.05). The addition of soursop leaves infusion at the dose of 400 mg / kg b.w. can increase HDL serum levels about 71% compared with positive control (p <0.05).Conclusion : Soursop leaves infusion decreased LDL serum levels and increased HDL serum levels of Wistar rats induced by HFFD.Keywords : Dyslipidemia, High fat and fructose diet, Soursop Leaves, HDL, LDL